Paternal Educational Strategies for Children’s Social Behavior in Female Migrant-Worker Families: A Qualitative Study Across Socioeconomic Groups - Faidin, Nahrul; Astuti, Tri Marhaeni Pudji; Prajanti, Sucihatiningsih Dian Wisika; Hardati, Puji (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Children’s social behavior in female migrant-worker families is shaped by how fathers reorganize caregiving, supervision, and everyday educational practices after maternal migration. However, previous research has more often emphasized the general consequences of parental migration than the class-sensitive pattern of paternal strategies used to guide children’s social behavior. This study, therefore, examined paternal educational strategies for children’s social behavior in female migrant-worker families across socioeconomic groups. The study used a qualitative descriptive design with purposive sampling and involved six fathers in Langgudu Sub-district, Bima Regency, Indonesia. Data were collected through semi-structured interviews, observation, and documentation, and were analyzed using thematic analysis. The findings show three interconnected strategies: role modeling, disciplinary education, and educational advice. In upper-socioeconomic families, fathers showed visible moral-religious role modeling and more structured daily discipline, but advice was often delivered in a harsh tone. In middle-socioeconomic families, fathers showed weaker direct role modeling and less structured discipline, while advice tended to be given gradually through verbal guidance. In lower-socioeconomic families, fathers showed strong work- and community-based role modeling, but discipline and advice were more reactive because work demands reduced supervision and routine consistency. These findings indicate that father involvement in migrant-worker families should be understood not only in terms of presence, but also in terms of the form, tone, and consistency of paternal educational practices. The study implies that schools, communities, and migrant-family support programs should strengthen constructive father engagement, routine-based caregiving, and nonviolent communication in left-behind families.